2009
DOI: 10.1192/apt.bp.105.001586
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic amnesia: when memory complaints are medically unexplained

Abstract: SummaryThe focus of this article is the assessment and management of medically unexplained (‘psychogenic’) amnesia, which we classify here as global or situation specific. Other psychiatric causes for memory disorder and neurological conditions that could cause diagnostic confusion are briefly reviewed, as are forensic aspects of memory complaints. Finally, brain and physiological mechanisms potentially associated with psychogenic amnesia are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
1
16
0
3
Order By: Relevance
“…Apart from dissociation, other psychological mechanisms, such as hyper-suppression or cognitive avoidance Lemogne et al, 2008;Tramoni et al, 2009) have been identified to underlie at times concurrently amnesic conditions, which are etiologically linked to psychological factors. These findings partly explain why some authors still favor the use of the term psychogenic amnesia over the term dissociative (McKay & Kopelman, 2009).…”
Section: Disturbances Of Eam Autonoetic Consciousness and Self In Psmentioning
confidence: 88%
“…Apart from dissociation, other psychological mechanisms, such as hyper-suppression or cognitive avoidance Lemogne et al, 2008;Tramoni et al, 2009) have been identified to underlie at times concurrently amnesic conditions, which are etiologically linked to psychological factors. These findings partly explain why some authors still favor the use of the term psychogenic amnesia over the term dissociative (McKay & Kopelman, 2009).…”
Section: Disturbances Of Eam Autonoetic Consciousness and Self In Psmentioning
confidence: 88%
“…Bei beiden Perspektiven sind vielmehr sehr ähnliche Mechanismen und Prozesse angesprochen, die innerhalb affektiver und kognitiver Untersuchungsparadigmata der Neuroscience gemeinsam studiert werden können [3]. Eine ganz analoge Haltung ist andererseits auch bei den strukturellen und funktionellen Gedächtnisstörungen angezeigt, die klinisch oft einander gegenübergestellt werden, jedoch auf identische neuronale Systeme und deren Funktionalität verweisen [69,72].…”
Section: Zur Psychopathologie Des Autobiografischen Gedächtnissesunclassified
“…Eine schwierige Differenzialdiagnose in der Abwägung »psychogener« vs. »organischer« Einflüsse kann sich zuweilen nach diskreten Schädel-Hirn-Traumata z. B. im Falle einer postkontusionellen Amnesie stellen [72].…”
Section: ■ ■unclassified
“…The term psychogenic amnesia describes a primary etiology of psychological stress without ignoring its neuroanatomical correlates. The use of terms such as functional or hysterical memory loss can be problematic and stigmatizing for patients (8). Of the types of psychogenic amnesia, the phenomenon of psychogenic fugue is perhaps the most psychologically determined.…”
Section: Discussionmentioning
confidence: 99%